Barriers to the adoption of BIM (building information modeling) in the Philippine construction industry - Sobreviñas, Xeena Grace M. (College of Engineering, University of the Philippines Diliman, 2018)
Building Information Modeling (BIM) is one of the technological advancements in the Architectural, Engineering, and Construction (AEC) industry which aims to be a tool to generate a digital representation of the physical and functional characteristics of a facility existing from the earliest conception to demolition. However, despite its promising advantages and benefits, the adoption of BIM in the construction industry is slower than anticipated or sometimes underused. This study aims to identify the current state of the BIM adoption in the Philippine construction industry and identify the barriers hindering BIM to be used at its full potential. BIM adoption in the Philippine Construction Industry is currently at Category III which involves partial utilization and partial integration wherein the 3D environment is managed with data attached using separate discipline-based BIM software tools used from the conceptualization up to the construction phase of the building life cycle. The implementation of BIM is considered to be at its nascent stages because construction related firms mostly just utilize the object modeling (3D) component of BIM and refuse to collaborate with other stakeholders. Meanwhile, the identified barriers to the BIM adoption is the lack of knowledge and skills about BIM and its tools, lack of financial resources, resistance to technological change, underused interoperability, BIM software limitations and lack of government involvement